Report of a Working Group on Umbellifer crops: Second Meeting, 26–28 June 2013, St. Petersburg, Russian Federation - Maggioni, L.; Geoffriau, E.; Allender, C.; Lipman, E.; Bioversity International (2014)
The second meeting of the ECPGR Umbellifer Crops Working Group (WG) was held 26-28 June 2013 at St. Petersburg, Russian Federation. The meeting, organized in collaboration with the N.I. Vavilov Research Institute of Plant Industry, brought together 15 participants from 11 countries. Reports were given on the status of national collections of umbellifer crops and updates were provided on ECPGR, AEGIS and EURISCO. Results of the AEGIS-funded project on “Assessment of Unique Material in European Collections of Umbellifer Crops” were presented and further steps for the selection of accessions to be included in the AEGIS European Collection were agreed. Regarding the crop-specific standards to be adopted by the WG as part of the AEGIS Quality System (AQUAS), the FAO Genebank standards endorsed in April 2013 were generally accepted with some additions/amendments. Minimum characterization descriptors were agreed for carrot. Specific lists will be developed for celeriac, celery, dill, parsley and parsnip. Collecting, characterization and evaluation activities carried out in the framework of the ECPGR-funded project on Umbellifer wild relatives were reported. Regarding the European Umbellifer Database (EUDB), and with the understanding that EURISCO will soon include characterization and evaluation data, it was recommended that the EUDB should not be further developed as a database for germplasm users but become a tool of the WG. It was agreed to organize the future activities of the WG in Phase IX around five main tasks, for which respective leaders were identified.